Mineral and bone disorders in conventional hemodialysis: Challenges and solutions. Issue 6 (13th June 2018) - Hamano, Takayuki
Abstract: Despite the advent of cinacalcet and noncalcium‐containing phosphate binders, controlling the progression of vascular calcification (VC) is still challenging. Recent reports demonstrate that carbamylation driven by high urea concentration aggravates VC, suggesting the importance of adequate dialysis in retarding its progression. Theoretically, other promising measures include the use of iron‐based phosphate binders, vitamin K, and magnesium supplements, which should be investigated in future randomized controlled trials (RCTs), ideally with hard outcomes. While incidence of hip fracture in patients on dialysis is decreasing in the United States and Japan (possibly owing to better control of PTH levels by cinacalcet) it remains much higher than that in the general population. Many drugs used in the treatment of osteoporosis, including bisphosphonate, raloxifene, denosumab, and teriparatide can, under specific conditions, increase bone mineral density (BMD), which is associated with a lower fracture rate. However, the efficacy of these drugs in reducing the fracture rate remains to be proven in hemodialysis (HD) patients, given their adverse effects such as severe hypocalcemia and resultant worsening of secondary hyperparathyroidism. Some clinical studies have shown that cinacalcet, lanthanum carbonate, and sevelamer reduce mortality in elderly patients on HD, suggesting the benefits of reducing PTH and serum phosphate levels. However, the target ranges of PTH and phosphate levels are based solely on observational studies. This is also the case when treating low PTH levels by decreasing vitamin D or calcium load. RCTs with hard clinical endpoints comparing different targets are necessary in the future.